A giant falls: The impact of evergrande on Asian stock indexes - Dora Almeida; Andreia Teixeira Marques Dionísio; Muhammad Enamul Haque; Paulo Ferreira (Journal of Risk and Financial Management, 2022)
The economic growth of China has been driven by the development of its real estate market, especially after the 2008 crisis. This growth is mostly related to the huge housing bubble and growing amounts of sovereign debt that have been redirected to corporations in the sector. Evergrande is one of those corporations; it is a Chinese company in the construction and real estate sector, a global giant with investments in many parts of the world. Its bond default in September 2021 sounded alerts in financial markets. Several news outlets spoke of the "next Lehman Brothers", and apprehension was very high, especially in Asian markets. This research work aims to evaluate the impact of Evergrande's bond default on six Asian stock markets, using an event study approach. The results show a strong reaction from the markets towards the event in study, even anticipating it. Furthermore, it is worth mentioning a quick reversion to "normal" behavior, indicating the rapid absorption of information by the markets.
Keywords: 650; event study; Asian stock markets; bond default; Evergrande; real estate